Inovasi Pendidikan: Optimalisasi Bimbingan Individual dalam Meningkatkan Pemahaman Guru terhadap Pembuatan Soal-Soal Pelajaran - Suparmi Suparmi (Jurnal Bintang Pendidikan Indonesia, 2024)
This study aims to enhance teachers' ability in composing lesson questions through the implementation of individual guidance. Conducted at Parungmulya Public Elementary School, the school action research involved 8 teachers over two cycles. The guidance process includes explaining the steps of question creation, teachers composing questions, and analyzing the results. The findings indicate a significant improvement in the ability to compose lesson questions. Teachers responded positively to individual guidance, stating assistance in composing lesson questions. In conclusion, this model can effectively enhance the quality of lesson question composition by teachers.